Child Grooming News Coverage: Psychological Communication of Nikita Mirzani’s Child on Instagram Social Media - Ruqqayah, Jelita; Ummu Salamah; Ismira Febrina (Journal of Communication Studies, 2025)
Grooming is a systematic action carried out by perpetrators to build closeness and trust with prospective victims to manipulate or exploit them. This study aims to analyze the impact of psychological communication received by Nikita Mirzani’s child involved in news coverage, both from the perspective of child developmental psychology and the social impact in their environment. This study used a descriptive method with a qualitative approach. Data collection techniques included interviews, observations on Instagram, literature studies, and documentation. The research results show the dimension of receiving stimuli through the senses: Informants learned about the Laura case from social media and further investigated to understand the events; the process mediating stimuli and responses triggered emotional and moral reflection, turned neutral attitudes critical and disappointed; predicted responses sparked initial empathy toward the perpetrator that then shifted to caution; sympathy moved toward the victim; affirmation of responses revealed that the victim’s behavior is influenced by the environment, intensive communication, and relationships